Towards fully automated identification of vesicle-membrane fusion events in TIRF microscopy. (21st September 2009) - Mele, Katarina; Vallotton, Pascal; Burchfield, James G.; James, David E.; , William E. Hughes
Total internal reflection fluorescence microscopy (TIRF-M) is imposing itself as the tool of choice for studying biological activity in close proximity to the plasma membrane. For example, the exquisite selectivity of TIRF-M allows monitoring the movement of GFP-tagged vesicles and their recruitment to the plasma membrane of cells. We present a novel computer vision system for automatically identifying elusive vesicle-plasma membrane fusion events. Our method is based on robust object tracking and matched filtering. It should accelerate the quantification of TIRF-M data and allow the extraction of more biological information from image data to support research in diabetes and obesity.